LANGUAGE TESTING: CHARACTERISTIC OF GOOD TESTS, TESTING LANGUAGE SKILLS AND COMPONENTS - Zananda, Tiray Febria; Setiawan, M. Lucky (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2023)
Tests can give contributions if it is use naturally. It is needed to do a test to know students’ ability. Tests are also used to measure ability in language. Language testing is a field of study under the umbrella of applied linguistics. The purpose of testing is to collect objective information that may be used in conjunction with subjective information to make better. Language test developers and teachers should think of new types of intensive tests to measure examinees’ real language competence and performance to make the tests more reliable. Tes dapat memberikan kontribusi jika digunakan secara alami. Perlu dilakukan tes untuk mengetahui kemampuan siswa. Tes juga digunakan untuk mengukur kemampuan berbahasa. Pengujian bahasa adalah bidang studi di bawah payung linguistik terapan. Tujuan pengujian adalah untuk mengumpulkan informasi obyektif yang dapat digunakan bersama dengan informasi subyektif untuk menjadikannya lebih baik. Pengembang tes bahasa dan guru harus memikirkan jenis tes intensif baru untuk mengukur kompetensi dan kinerja bahasa peserta ujian yang sebenarnya agar tes tersebut lebih dapat diandalkan.